Impact of gamma-ray irradiation on commercial silicon carbide MOSFET with boost converter application - S. M. Abd El-Azeem; W. Abd El-Basit (Power Electronic Devices and Components)
This paper study impact of gamma-ray irradiation on the characteristics of silicon carbide power metal oxide semiconductor field effect transistor (SiC MOSFET) from CREE, Inc., and its corresponding effects on the operation of 5/12 V DC-DC boost converter. The proposed 10 A (C2M0280120D) SiC MOSFET was irradiated by gamma-ray irradiation with a dose rate of 0.99 kGy/h ranging from 0 to 6 kGy. The performance of the circuit in terms of the output voltage, power, as well the converter efficiency was studied before and after SiC MOSFET being irradiated. It was observed after 2kGy the proposed boost converter circuit unaffected by gamma-ray radiation. Therefore, at 2 kGy, the 5/12 VDC boost converter output voltage, power, as well the converter efficiency increases by 17.64 %, 38.42 %, and 22.25 %, respectively from their initial values before irradiation. These increases were believed to be due to the decreases in the threshold voltage, on-state resistance, input, output and reverse transfer-capacitances, as well figure of merit and total gate charge of the SiC MOSFET which were caused by the defects introduced inside the semiconductor during the irradiation and also decreasing of switching times and conduction losses of SiC MOSFET after being irradiated. Finally, the converter circuit stability was increased, whenever the circuit switch exposed to gamma doses up to 2 kGy. Where, during the range of selected gamma doses, the value of energy factor variation was always lower than the energy factor, which means that the proposed converter is stable.